Theatre reception in Greece and the ideology of greekness - Angelopoulos, Tasos (Amfiteater (Ljubljana), 2019)
The article presents an example of how the social and political ideology of Greekness has determined the way the Greek audience and critics interpret performances of Aristophanes's ancient comedies. Starting from the comparison of the director Nikos Karathanos's performance of Aristophanes's The Birds (2016) with Karolos Koun's performance of the same name in 1959, the article argues that Koun's The Birds imposed a specific aspect on Greekness , functioning as "dominant rule" even today. The article, integrated into a sociological aspect on theatre, suggests that each theatre performance transfers much more extra-theatrical (mostly social and ideological) meaning than we may believe and the interpretation of each specific theatrical action/reaction also passes through the understanding of the society in which it belongs.
Keywords: Aristofan; Aristophanes; comedies; družba; gledališče; Greekness; grštvo; ideologija; ideology; Karolos Koun; komedije; Nikos Karathanos; Ptiči; society; The birds; theatre